Questioning the environmental stress hypothesis for gall diversity of restinga vegetation on dunes - Arriola, Ígor; Melo Jr., João Carlos F.; Isaias, Rosy Mary S. (Revista de Biología Tropical, 2015)
The Atlantic Coast Restinga is a mosaic of plant communities with a distinct floristic and phytophysiognomy, exposed to luminous, thermal, and saline stresses. Plants of the restinga must have special features commonly associated to xeric environments, and are expected to host a high diversity of galling herbivores. We studied gall morphotypes, and recorded the diversity of galls on plants growing in sand dunes in a remnant area of restinga (Acaraí State Park) in São Francisco do Sul, Santa Catarina State, Brazil. The sampling was done in four plots (250 x 5 m), constituting a total area of 5 000 m², during April, May and June. Plant branches (n ≥ 5) with galls were sampled, identified, and the galls were photographed. The galls were classified into eight morphotypes, associated to eight host plants constituting 15 host plants - galling herbivores systems. The identification of the gall - inducers was based on literature, and on the species-specific feature of this kind of host plant-gall inducers interaction. There was a predominance of leaf galls, green in color. The most common morphotypes were the globoid, lenticular, conical, rosette, marginal, and fusiform galls, similarly to the inventories performed on other Brazilian biomes. Despite the environmental stresses, the xeric features of the dunes of the ASP, and the high local plant diversity, the diversity of galling herbivores were low. Varronia curassavica (Boraginaceae), Smilax campestris (Smilacaceae), and Guapira opposita (Nyctaginaceae) were superhosts of galling herbivores in the dunes, with about 70 % of the total associated parasites. The environmental effect seems to be neutral, either for the host plants or for the generation of gall morphotypes. Alternatively, the scarce nutritional resources could be restrictive for the establishment of the galling herbivores inside plant tissues.